UN SECRETARY- GENERAL'S FORMS OF INVOLVEMENT IN THE PEACEFUL SETTLEMENT OF INTERNATIONAL DISPUTES. THE DIPLOMATIC MEANS - Oana-Adriana IACOB⃰ (Challenges of the Knowledge Society)
The United Nations Secretary- General is a symbol and an instrument of the peaceful settlement of international disputes, with a proven effectiveness in the prevention and resolution of conflicts, even in the most difficult political contexts. The configuration of this distinguished function is largely the result of a long evolutionary process which ultimately provided the occupants with a repertoire of practices that define a powerful and influential role in maintaining the international peace and security. The UN Secretary General’s endeavours in the field of peaceful resolution of conflicts may include traditional diplomatic means, such as good offices, mediation and international inquires. Nevertheless, sometimes the traditional techniques of diplomatic approach require the complementary use of unofficial, discreet diplomatic means (such as secondary diplomacy - track two diplomacy - and hybrid diplomacy - track one and a half diplomacy)which may enable a superior information and trigger new ways of action. The present study aims to explore the political and diplomatic means, as forms of involvement of the UN Secretary-General in the peaceful settlement of international disputes and as part of the wider and powerful role in the maintenance of international peace and security.